Belajar Bahasa Inggris melalui Percakapan Dasar bagi Siswa Madrasah Tsanawiyah - Dedi Aprianto; Zainudin Abdussamad; Lela Rahmawati (Insan Kreasi Media, 2023)
A language profiency must have been learnt or taught since early ages and speaking skills are the prominent to conquer the global world as it is a main means of communication. The community service was held to aim at developing students’ speaking profiency through teaching them with basic English conversation materials. It was carried out solving several critical problems in ELT for the school students as the beginners. the community service was done through 4 steps; Identifing problems, planning the program, executing the program, and evaluating the program. ELT was conducted by using English training by teaching the students with the use of three communicative methods. The results of an English Learning program executed suggest that the effectiveness of using basic English conversation materials contribute to develop students’ sepaking proficiency positively-enough. The program’s effectiveness can be seen the teachers’ evaluation of Teaching and Learning Process done (79,38%) and the students’ evaluation of Learning process can be (75,51%). The program is carried out at aming preparing the students with good English profiency for further English learning levels.